Aspek Teologis dan Pedagogis Katekismus Heidelberg dalam Pendidikan Agama Kristen di Sekolah - Irene Florencia Christin Lawalata; George Sulaiman Malelak (Verbum Christi: Jurnal Teologi Reformed Injili, 2026)
In its historical development, objections have been raised that the Heidelberg Catechism is not adapted to children, either in their intellectual capacity or religious experience. Therefore, the writer analyzes the theological and pedagogical aspects of the Heidelberg Catechism in Christian Education, along with modern pedagogy critiques. From the analysis, the writer concludes that the Heidelberg Catechism possesses strong significance for Christian Education. Its content not only fosters a love for doctrinal instruction but also shapes students’ critical and spiritual awareness to respond to God’s covenant through faith and repentance, and to grasp the true meaning of living as Christians. This conclusion brought us to see the further reflection on the pedagogical significance inherent in embracing the Heidelberg Catechism within educational contexts. In this article, the writer deals with two Heidelberg Catechism’ pedagogical significances, Christ-centered teaching, and consistent Reformed instruction.